A Critical Study of Ill-Health (Oria) and Treatment of Diseases (Igwo Oria) in Igbo Society: Focus on Traditional Medicine - Johnmajor Chinecherem Nwaozuru (Darul Yasin Al Sys, 2026)
Life (Ndu) is regarded in Igbo society as God-given (Chinenye Ndu) and is therefore held in high esteem, requiring protection, care, and preservation. This belief explains why murder (Igbu Ochu) is forbidden and why individuals seek proper treatment when affected by ill health (Oria). This study examines the significance of traditional medicine in sustaining good health in Igbo society and highlights the declining patronage of indigenous medical practices in recent times. The study is motivated by the growing preference for Western medicine among many Igbo people, including some Christians who perceive the use of indigenous medicinal herbs, roots, leaves, fruits, and consultation with traditional medical practitioners as a deviation from religious faith or a form of syncretism. Using secondary sources of data, including books, journal articles, textbooks, newspapers, and other relevant written materials, the study explores indigenous medicinal knowledge and the roles of various traditional health practitioners, including traditional medicine men (Ndi Dibia mgborogwu na mkpa akwukwo), traditional birth attendants (Ndi na-amu nwa), and traditional bone setters (Ndi na-agba okpukpu). The findings indicate a decline in the use of traditional medicine in Igbo society, despite its historical importance in the treatment of diseases (Igwo Oria) and its continuing relevance amid concerns about fake drugs, deteriorating public health facilities, frequent health-sector strikes, and the high cost of formal healthcare. The study concludes that traditional medicine remains an important component of health preservation in Igbo society and should not be dismissed in favor of Western medicine alone. It recommends a complementary approach that integrates traditional and Western medicine to strengthen healthcare delivery, improve access to treatment, and promote healthy living among Igbo people and the wider Nigerian population.